Nanotechnology in Chronic Pain Relief - Chen, Jing; Jin, Teng; Zhang, Hua (Frontiers in Bioengineering and Biotechnology, 2020)
Increasing awareness of chronic pain due to both injury and disease have encouraged drug companies and pharmaceutical researchers alike to design and fabricate better, more specific drugs for pain relief. However, overuse of clinically available pain medication has caused a multitude of negative repercussions, including drug tolerance, addiction, and other severe side effects, which can prolong suffering and reduce pain mediation. Applications of nanotechnology to the field of drug delivery has sought to enhance the treatment efficiency, lower side effects, and mitigate the formation of tolerance. The use of nanomaterials has several advantages for chronic pain relief, such as controlled release, prolonged circulation time, and limited side effects. With the development of nanotechnology, strategies for chronic pain relief have also bourgeoned utilizing a variety of nanomaterials and targeting surface modifications. In addition to using these materials as carriers for drug delivery, nanomaterials can also be designed to have inherent properties that relieve chronic pain. This minireview covers the current status of designed nanomaterials for pain relief and provides a discussion of future considerations for nanotechnology designed for relieving chronic pain.